Development of the project-level Women’s Empowerment in Agriculture Index (pro-WEAI) - Malapit, Hazel J.; Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Seymour, Greg; Martinez, Elena M.; Heckert, Jessica; Rubin, Deborah; Vaz, Ana; Yount, Kathryn M.; Gender, Agriculture, and Assets Project, Phase 2 (GAAP2) Study Team; Myers, Emily; Pereira, Audrey; et al. (Elsevier, 2019)
With growing commitment to women’s empowerment by agricultural development agencies, sound methods and indicators to measure women’s empowerment are needed to learn which types of projects or project-implementation strategies do and do not work to empower women. The Women’s Empowerment in Agriculture Index (WEAI), which has been widely used, requires adaptation to meet the need for monitoring projects and assessing their impacts. In this paper, the authors describe the adaptation and validation of a project-level WEAI (or pro-WEAI) that agricultural development projects can use to identify key areas of women’s (and men’s) disempowerment, design appropriate strategies to address identified deficiencies, and monitor project outcomes related to women’s empowerment.